Plastic waste associated with the COVID-19 pandemic: Crisis or opportunity? - Khoo, Kuan Shiong; Ho, Lih Yiing; Lim, Hooi Ren; Leong, Hui Yi; Chew, Kit Wayne (Journal of hazardous materials, 2021)
Coronavirus Diseases 2019 (COVID-19) pandemic has a huge impact on the plastic waste management in many countries due to the sudden surge of medical waste which has led to a global waste management crisis. Improper management of plastic waste may lead to various negative impacts on the environment, animals, and human health. However, adopting proper waste management and the right technologies, looking in a different perception of the current crisis would be an opportunity. About 40% of the plastic waste ended up in landfill, 25% incinerated, 16% recycled and the remaining 19% are leaked into the environment. The increase of plastic wastes and demand of plastic markets serve as a good economic indicator for investor and government initiative to invest in technologies that converts plastic waste into value-added product such as fuel and construction materials. This will close the loop of the life cycle of plastic waste by achieving a sustainable circular economy. This review paper will provide insight of the state of plastic waste before and during the COVID-19 pandemic. The treatment pathway of plastic waste such as sterilisation technology, incineration, and alternative technologies available in converting plastic waste into value-added product were reviewed. [Display omitted] •Sudden surge of medical waste has a huge impact on the plastic waste management.•3R’s implementation requires the support from various sector.•Convert plastic waste into value-added product: fuel and construction materials.